Bi2Mo3O12 / VC photoelectrocatalytic photo-anode deposited on carbon cloth substrate and method
By depositing Bi2Mo3O12/VC composite materials on the carbon cloth substrate and growing in layers using pulse arc pulse discharge technology, the problems of difficulty in preparing materials such as bismuth molybdate and insufficient catalytic performance in the prior art are solved, and efficient photoelectrocatalytic oxygen evolution performance is achieved.
Patent Information
- Application Number
- CN202510118530.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively improve the photoelectrocatalytic performance in hydrogen production, especially in the preparation and application of materials such as bismuth molybdate and insufficient catalytic performance.
By depositing Bi2Mo3O12/VC composite materials on the carbon cloth substrate, the pulse arc pulse discharge technology is used to grow in layers to form heterostructures to improve the photoelectrocatalytic performance.
The efficient preparation of Bi2Mo3O12/VC photocatalytic photoanode is achieved, the material structure is controllable, and the excellent photocatalytic oxygen evolution performance is shown, especially in alkaline solutions.
Smart Images

Figure CN119843318A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of composite photoelectrocatalytic photoanode materials, and specifically relates to a Bi- 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode and method. Background Art
[0002] Hydrogen has attracted much attention due to its high combustion heat and clean combustion products. There are many ways to produce hydrogen. Using PEC cells to drive water decomposition reactions is a relatively convenient and quick way to produce hydrogen. PEC cells can convert solar energy into chemical energy cleanly and sustainably. Fujishima and Honda found that TiO 2 After the photoelectrode catalyzed water splitting reaction, technicians have been committed to developing efficient metal oxides as photoelectrodes for PEC cells to drive water splitting reactions.
[0003] The general formula of Aurivillius phase layered oxides is [Bi 2 O 2 ][A n–1 B n O 3n+1 ] (n is the perovskite layer, A is the alkali metal, and B is the transition metal), common ones include Bi 2 MoO 6 (n=1, 2, 3), Bi 2 WO 6 (n=1), BiVO 4 (n=1), etc. When n is a fraction, it is a mixed-phase Aurivillius compound. Among them, bismuth molybdate is a typical Aurivillius compound. As the number of perovskite layers continues to increase, its preparation becomes more and more difficult. It is well known that the Aurivillius layered perovskite family has excellent ferroelectric properties, which is beneficial to promote the separation and migration of photogenerated carriers in the photocatalytic process.
[0004] Bismuth molybdate is a common N-type direct bandgap semiconductor material in Bi-based multi-component oxides. Bismuth molybdate materials exist in three crystalline phases, which can be expressed by the general structural formula Bi 2 O 3 ·Mo n O 3n Different n values correspond to three different crystal phases. When n=3, the structure is α phase (Bi 2 Mo 3 O 12 ), the α phase is usually described as a defective scheelite structure containing three non-equivalent MoO 4Unit. Transition metal carbides (TMCs) are widely used in chemical engineering, electronic devices and other fields due to their advantages such as high conductivity, high hardness, acid and alkali resistance, and good thermal stability. Studies have found that TMCs nanomaterials can promote the adsorption and desorption of hydrogen due to their special d-band electron configuration and exposed active sites, thereby showing high catalytic hydrogen and oxygen evolution activity. As a transition metal carbide, VC has a similar d-band electronic state density to Pt, lower impedance, and better hydrogen adsorption performance, and can be used as a new catalyst to replace Pt. The carbon cloth substrate has a high specific surface area, which further increases the exposure of the active sites of the product, which is beneficial to the improvement of the photoelectrocatalytic performance.
[0005] Therefore, if Bi 2 Mo 3 O 12 Compounded with VC, and then further grown on a carbon cloth substrate, so that in theory Bi 2 Mo 3 O 12 It will form a certain heterostructure with VC, which can effectively improve the photoelectrocatalytic performance and prepare a composite photoelectrocatalytic photoanode with good performance, but there is no related report yet. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a Bi deposited on a carbon cloth substrate. 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode and method, simple operation, controllable conditions, Bi 2 Mo 3 O 12 and VC composite, and layered growth on a carbon cloth substrate by pulsed arc discharge deposition technology. 2 Mo 3 O 12 The structure of the / VC / carbon cloth photoelectrocatalytic photoanode material is controllable and exhibits good photoelectrocatalytic oxygen evolution performance in alkaline solution.
[0007] The present invention is achieved through the following technical solutions: A method for depositing Bi on a carbon cloth substrate 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode method, comprising the following steps: S1, dissolving bismuth hydroxide with nitric acid to obtain a mixed solution, adding the mixed solution and oxalic acid to an ammonium molybdate solution and stirring, wherein the mass ratio of bismuth hydroxide, oxalic acid and ammonium molybdate in the ammonium molybdate solution is 0.26: (0.05-0.4): (0.196-0.588), to obtain a sol; S2, removing the solvent from the sol and grinding it, then heat-treating it at 300-800 ° C under the protection of an inert atmosphere, and then grinding it to obtain Bi 2 Mo 3 O 12 Powder, Bi 2 Mo 3 O 12 The powder and the VC powder are dispersed and iodine is introduced into the powder in sequence to obtain a first precursor solution and a second precursor solution; S3, using the pulse arc discharge technology, using the first precursor liquid and the second precursor liquid to deposit Bi on the pickled carbon cloth in sequence 2 Mo 3 O 12 and VC, voltage is 300-600 V, each deposition is 10-50 min, Bi is deposited on the carbon cloth substrate 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode, and then dried to obtain Bi deposited on the carbon cloth substrate 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode.
[0008] Preferably, S1 disperses bismuth hydroxide in ethylene glycol first, and then adds nitric acid to dissolve it to obtain a mixed solution; The solvent of the ammonium molybdate solution is ethylene glycol.
[0009] Furthermore, the ratio of bismuth hydroxide to ethylene glycol is 0.26 g: 10-40 mL, nitric acid is added to adjust the pH to 3-9, and then stirred until completely dissolved to obtain a mixed solution; In the ammonium molybdate solution, the ratio of ammonium molybdate to ethylene glycol is (0.196-0.588) g: (10-40) mL.
[0010] Preferably, S1 adds the mixed solution and oxalic acid into the ammonium molybdate solution and stirs for 4-24 h to obtain a sol.
[0011] Preferably, S2 heats the sol at 100-160 °C for 2-18 h, grinds it evenly, and finally performs a heat preservation treatment at 300-800 °C.
[0012] Furthermore, the heat preservation treatment described in S2 is carried out at 300-800 °C for 2-6 h, wherein the temperature is increased from room temperature to 300-800 °C at a heating rate of 5-20 °C / min.
[0013] Preferably, the VC powder described in S2 is obtained by the following steps: Vanadium tetrachloride and carbon powder are uniformly mixed in a mass ratio of (0.5-3):(1-6), and then heated from room temperature to 800-1000 °C at a rate of 5-20 °C / min under the protection of an inert atmosphere, and kept at 800-1000 °C for 2-4 h. After the product is cooled, it is ground to obtain VC powder; The pickled carbon cloth described in S3 is obtained by the following steps: The carbon cloth was cut into pieces with a length of 20-60 mm and a width of 10-40 mm. The pieces were then immersed in acetone, 3-6 mol / L HCl solution, deionized water and anhydrous ethanol for ultrasonic treatment for 15-30 min to obtain acid-washed carbon cloth.
[0014] Preferably, S2 will be 0.1-0.6 g Bi 2 Mo 3 O 12 The powder is added to 30 mL-80 mL of isopropanol and dispersed evenly, and then 0.1-0.6 g of iodine is added and stirred until evenly dispersed to obtain a first precursor solution; S2: add 0.1-0.6 g VC powder to 0.005-0.05 g polyvinyl pyrrolidone and disperse evenly, then add 0.1-0.6 g iodine and stir until evenly dispersed to obtain a second precursor solution.
[0015] Preferably, S3 arranges the pickled carbon on the negative electrode of the pulse arc discharge instrument, and the positive electrode uses graphite, which is deposited at 80-150 ° C, and Bi is deposited on the carbon cloth substrate. 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode.
[0016] A method of depositing Bi on a carbon cloth substrate according to any one of the above 2 Mo 3 O 12 Bi deposited on a carbon cloth substrate obtained by the method of / VC photoelectrocatalytic photoanode 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode.
[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention is a method for depositing Bi on a carbon cloth substrate 2 Mo 3 O 12 By adjusting the dosage of bismuth hydroxide, oxalic acid and ammonium molybdate, a simple sol-gel method can be used to prepare Bi / VC photoelectrocatalytic photoanode. 2 Mo 3 O12 The powder has good crystallinity, high product purity and easy control of reaction conditions. 2 Mo 3 O 12 After the powder and VC powder are dispersed in sequence, iodine is introduced and the Bi 2 Mo 3 O 12 The precursor solution and VC precursor solution are sequentially deposited on the carbon cloth substrate after acid washing. 2 Mo 3 O 12 and VC, Bi obtained by this gradient deposition method 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode material, also a gradient coating, Bi 2 Mo 3 O 12 / VC photoelectrocatalytic materials grow on carbon cloth substrates to form self-supporting photoelectrocatalytic photoanode materials that can make Bi 2 Mo 3 O 12 The VC and the carbon cloth cooperate with each other to achieve the separation of photogenerated carriers at a lower bias voltage. The high specific surface area of the carbon cloth substrate also increases the exposure of active sites, which is conducive to further improving the photoelectrocatalytic performance and the overall catalytic performance. The change of deposition voltage and time can control the deposition thickness, making Bi 2 Mo 3 O 12 / VC structure is controllable and is a highly efficient PEC catalytic material. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode, with carbon cloth material as the conductive matrix, makes the interface bond firmly, and at the same time the heterogeneous structure forms a certain built-in electric field, which can promote the separation of photogenerated carriers and improve the photoelectrocatalytic efficiency. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode exhibits excellent photoelectrocatalytic oxygen production performance in alkaline electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Bi prepared under the conditions of Example 2 of the present invention 2 Mo 3 O 12 XRD pattern of .
[0019] Figure 2 This is the XRD pattern of VC prepared under the conditions of Example 2 of the present invention.
[0020] Figure 3 Bi prepared under the conditions of Example 2 of the present invention 2 Mo 3 O 12 SEM photo of / VC / carbon cloth.
[0021] Figure 4 Bi prepared under the conditions of Example 2 of the present invention 2 Mo 3 O 12 LSV performance diagram of oxygen evolution of / VC / carbon cloth under alkaline conditions.
[0022] Figure 5 Bi prepared under the conditions of Example 2 of the present invention 2 Mo 3 O 12 External bias-photoelectric conversion efficiency curve of / VC / carbon cloth. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0024] The present invention is a method for depositing Bi on a carbon cloth substrate 2 Mo 3 O 12 / VC photoelectrocatalytic photoanode method, specifically comprising the following steps: Step 1, 0.26 g of bismuth hydroxide and 0.196-0.588 g of ammonium molybdate are prepared at a molar ratio of 2:(2-6), the bismuth hydroxide is dispersed in 10-40 mL of ethylene glycol, nitric acid is added to adjust the pH to 3-9, and stirred until completely dissolved, which is recorded as solution A; Step 2, dissolving ammonium molybdate in 10-40 mL of ethylene glycol, stirring until completely dissolved, recorded as solution B, slowly adding solution A to solution B, adding 0.05-0.4 g of oxalic acid at the same time, stirring for 4-24 h to form sol C; Step 3, after heating sol C in an oven at 100-160 ° C for 2-18 h, the solvent is evaporated to obtain a dry gel, the dry gel is placed in a mortar and ground evenly, placed in a white magnetic boat, and placed in a tubular furnace. Under the protection of an inert atmosphere of Ar, the temperature is raised from room temperature to 300-800 ° C at a rate of 5-20 ° C / min, and the temperature is kept for 2-6 h. After the product is cooled, it is taken out and ground to obtain powder D, namely Bi 2 Mo 3 O 12 Powder; Step 4, vanadium tetrachloride and carbon powder are prepared in a mass ratio of (0.5-3): (1-6), mixed evenly, placed in a graphite crucible, placed in a tubular furnace, and heated from room temperature to 800-1000 ° C at a heating rate of 5-20 ° C / min under the protection of an inert atmosphere of Ar, and kept warm for 2-4 h. After the product is cooled with the furnace, it is ground to obtain powder E, that is, VC powder. The VC material is prepared by a one-step calcination method, which has a simple process, low operation difficulty, and easy process control.
[0025] Step 5, weigh 0.1-0.6 g of powder D and 0.1-0.6 g of powder E and place them in beakers respectively, then add 30 mL-80 mL of isopropanol and 0.005-0.05 g of PVP (polyvinyl pyrrolidone) respectively, stir until uniformly dispersed, then add 0.1-0.6 g of iodine and continue stirring until uniformly dispersed, to obtain Bi 2 Mo 3 O 12 Precursor solution and VC precursor solution; Step 6, cut the carbon cloth substrate into pieces with a length of 20-60 mm and a width of 10-40 mm, and then completely immerse the carbon cloth substrate in acetone, 3-6 mol / L HCl solution, deionized water, and anhydrous ethanol in sequence, and perform ultrasonic treatment for 15-30 min respectively.
[0026] Step 7: Place the treated carbon cloth substrate on the negative electrode of the pulse arc discharge instrument, and use a 20*10*3 mm graphite substrate as the positive electrode. Set the voltage to 300-600 V and the deposition temperature to 80-150 °C. Turn on the equipment, deposit the VC precursor solution for 10-50 min, and then replace the Bi 2 Mo 3 O 12 The precursor solution continues to deposit for 10-50 min, then the equipment is turned off, the carbon cloth substrate is taken out, and the required Bi is obtained after drying. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode. Example 1 Step 1, 0.26 g of bismuth hydroxide and 0.196 g of ammonium molybdate are prepared, the bismuth hydroxide is dispersed in 10 mL of ethylene glycol, nitric acid is added to adjust the pH to 3, and stirred until completely dissolved, which is recorded as solution A; Step 2, dissolve ammonium molybdate in 10 mL of ethylene glycol and stir until completely dissolved, which is recorded as solution B. Slowly add solution A into solution B, and add 0.05 g of oxalic acid at the same time, and stir for 4 h to form sol C; Step 3, after heating sol C in an oven at 100 °C for 2 h, the solvent was evaporated to obtain a dry gel, the dry gel was placed in a mortar and ground evenly, placed in a white magnetic boat, and placed in a tubular furnace. Under the protection of an inert atmosphere of Ar, the temperature was raised from room temperature to 300 °C at a rate of 5 °C / min, and the temperature was kept for 2 h. After the product was cooled, it was taken out and ground to obtain powder D, namely Bi 2 Mo 3 O 12 Powder; Step 4, vanadium tetrachloride and carbon powder are prepared in a mass ratio of 0.5:1, mixed evenly, placed in a graphite crucible, placed in a tubular furnace, and heated from room temperature to 800 °C at a rate of 5 °C / min under the protection of an inert atmosphere of Ar, and kept warm for 2 h. After the product is cooled with the furnace, it is ground to obtain powder E, that is, VC powder; Step 5: Weigh 0.1 g of powders D and E and place them in beakers, then add 30 mL of isopropanol and 0.005 g of PVP (polyvinyl pyrrolidone) respectively, stir until evenly dispersed, then add 0.1 g of iodine and continue stirring until evenly dispersed to obtain Bi 2 Mo 3 O 12 Precursor solution and VC precursor solution; Step 6, take the carbon cloth substrate and cut it into 20 mm in length and 10 mm in width, then immerse the carbon cloth substrate completely in acetone, 3 mol / L HCl solution, deionized water, and anhydrous ethanol in sequence, and ultrasonically treat them for 15 min respectively.
[0027] Step 7: Place the treated carbon cloth substrate on the negative electrode of the pulse arc discharge instrument, and use a 20*10*3 mm graphite substrate as the positive electrode. Set the voltage to 300 V and the deposition temperature to 80 °C. Turn on the equipment, deposit the VC precursor solution for 10 min, and then replace the Bi 2 Mo 3 O 12 The precursor solution was deposited for 10 min, then the equipment was turned off, the carbon cloth substrate was taken out, and the desired Bi was obtained after drying. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode. Example 2 Step 1, 0.26 g of bismuth hydroxide and 0.392 g of ammonium molybdate are prepared, the bismuth hydroxide is dispersed in 20 mL of ethylene glycol, nitric acid is added to adjust the pH to 7, and stirred until completely dissolved, which is recorded as solution A; Step 2, dissolve ammonium molybdate in 30 mL of ethylene glycol and stir until completely dissolved, which is recorded as solution B. Slowly add solution A into solution B, and add 0.1 g of oxalic acid at the same time, and stir for 12 h to form sol C; Step 3, after heating sol C in an oven at 140 °C for 12 h, the solvent was evaporated to obtain a dry gel, the dry gel was placed in a mortar and ground evenly, placed in a white magnetic boat, and placed in a tubular furnace. Under the protection of an inert atmosphere of Ar, the temperature was raised from room temperature to 500 °C at a rate of 10 °C / min, and the temperature was kept for 4 h. After the product was cooled, it was taken out and ground to obtain powder D, namely Bi 2 Mo 3 O 12 Powder; Step 4, vanadium tetrachloride and carbon powder are prepared in a mass ratio of 1:4, mixed evenly, placed in a graphite crucible, placed in a tubular furnace, and heated from room temperature to 900 ° C at a heating rate of 10 ° C / min under the protection of an inert atmosphere of Ar, and kept warm for 3 hours. After the product is cooled with the furnace, it is ground to obtain powder E, that is, VC powder; Step 5, weigh 0.3 g of powder D and E and place them in a beaker, then add 50 mL of isopropanol solution and 0.01 g of PVP (polyvinyl pyrrolidone) respectively, stir until uniformly dispersed, and then add 0.3 g of iodine and continue stirring until uniformly dispersed to obtain Bi 2 Mo 3 O 12 Precursor solution and VC precursor solution; Step 6, take the carbon cloth substrate and cut it into 40 mm in length and 20 mm in width, then immerse the carbon cloth substrate completely in acetone, 5 mol / L HCl solution, deionized water, and anhydrous ethanol in sequence, and ultrasonically treat them for 20 min respectively.
[0028] Step 7: Place the treated carbon cloth substrate on the negative electrode of the discharge deposition instrument, and use a 20*10*3 mm graphite substrate as the positive electrode. Set the voltage to 400 V and the deposition temperature to 100 °C. Turn on the equipment, deposit the VC precursor solution for 30 min, and then replace the Bi 2 Mo 3 O 12 The precursor solution was deposited for 30 min, then the equipment was turned off, the carbon cloth substrate was taken out, and the desired Bi was obtained after drying. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode.
[0029] Depend on Figure 1 It can be seen that the generated powder can correspond well to the PDF78-2420 card, which is a good indication that Bi2 Mo 3 O 12 Powder.
[0030] Depend on Figure 2 It can be seen that the generated powder can correspond well to the PDF73-0476 card, thus well indicating that VC powder was generated.
[0031] Depend on Figure 3 It can be seen that there are large pieces of VC powder and Bi on the carbon fiber. 2 Mo 3 O 12 Flake powder, indicating Bi 2 Mo 3 O 12 Successfully grown with VC on carbon cloth.
[0032] The oxygen evolution LSV performance test was carried out in a 1 M sodium borate solution with a pH of about 9.5. Figure 4 It can be seen that under alkaline conditions, the overpotential of the composite electrocatalyst can reach 0.738 mA / cm at 1.23 V. 2 .
[0033] Figure 5 The applied bias voltage-photoelectric conversion efficiency is to analyze the Bi deposited on the carbon cloth substrate. 2 Mo 3 O 12 When the PEC water splitting performance of the / VC photoelectrocatalytic photoanode is calculated by applying a small bias voltage using an external power supply, the ABPE reaches a maximum value of about 0.1% when the overpotential is about 1.0. Example 3 Step 1, 0.26 g of bismuth hydroxide and 0.588 g of ammonium molybdate are prepared, the bismuth hydroxide is dispersed in 40 mL of ethylene glycol, nitric acid is added to adjust the pH to 9, and the mixture is stirred until completely dissolved, which is recorded as solution A; Step 2, dissolve ammonium molybdate in 40 mL of ethylene glycol and stir until completely dissolved, which is recorded as solution B. Slowly add solution A into solution B, and add 0.4 g of oxalic acid at the same time, and stir for 24 h to form sol C; Step 3, after heating sol C in an oven at 160 °C for 18 h, the solvent was evaporated to obtain a dry gel, the dry gel was placed in a mortar and ground evenly, placed in a white magnetic boat, and placed in a tubular furnace. Under the protection of an inert atmosphere of Ar, the temperature was raised from room temperature to 800 °C at a rate of 20 °C / min, and the temperature was kept for 6 h. After the product was cooled, it was taken out and ground to obtain powder D, namely Bi 2 Mo 3 O 12 Powder; Step 4, vanadium tetrachloride and carbon powder are prepared in a mass ratio of 3:6, mixed evenly, placed in a graphite crucible, placed in a tubular furnace, and heated from room temperature to 1000 ° C at a rate of 20 ° C / min under the protection of an inert atmosphere of Ar, and kept warm for 4 h. After the product is cooled with the furnace, it is ground to obtain powder E, that is, VC powder; Step 5, weigh 0.6 g of powder D and E and place them in a beaker, then add 80 mL of isopropanol solution and 0.05 g of PVP (polyvinyl pyrrolidone) respectively, stir until evenly dispersed, then add 0.6 g of iodine and continue stirring until evenly dispersed, to obtain Bi 2 Mo 3 O 12 Precursor solution and VC precursor solution; Step 6, take the carbon cloth substrate and cut it into 60 mm in length and 40 mm in width, then immerse the carbon cloth substrate completely in acetone, 6 mol / L HCl solution, deionized water, and anhydrous ethanol in sequence, and ultrasonically treat them for 30 min respectively.
[0034] Step 7: Place the treated carbon cloth substrate on the negative electrode of the pulse arc discharge instrument, and use a 20*10*3 mm graphite substrate as the positive electrode. Set the voltage to 600 V and the deposition temperature to 150 °C. Turn on the equipment, deposit the VC precursor solution for 50 min, and then replace the Bi 2 Mo 3 O 12 The precursor solution was deposited for 50 min, then the equipment was turned off, the carbon cloth substrate was taken out, and the desired Bi was obtained after drying. 2 Mo 3 O 12 / VC / carbon cloth photoelectrocatalytic photoanode.
Claims
1. A method for depositing Bi2Mo3O on a carbon cloth substrate 12 / VC photoelectrocatalytic photoanode method, characterized in that, The following steps are involved: S1, dissolving bismuth hydroxide with nitric acid to obtain a mixed solution, adding the mixed solution and oxalic acid to an ammonium molybdate solution and stirring, wherein the mass ratio of bismuth hydroxide, oxalic acid and ammonium molybdate in the ammonium molybdate solution is 0.26: (0.05-0.4): (0.196-0.588), to obtain a sol; S2, removing the solvent from the sol and grinding it, then heat-treating it at 300-800 °C under an inert atmosphere, and grinding it again to obtain Bi2Mo3O 12 Powder, Bi2Mo3O 12 The powder and the VC powder are dispersed and iodine is introduced into the powder in sequence to obtain a first precursor solution and a second precursor solution; S3, using the pulse arc discharge technology, using the first precursor liquid and the second precursor liquid to deposit Bi2Mo3O on the pickled carbon cloth in sequence 12 and VC, voltage of 300-600 V, each deposition time of 10-50 min, Bi2Mo3O is deposited on the carbon cloth substrate 12 / VC photoelectrocatalytic photoanode, and then dried to obtain Bi2Mo3O deposited on the carbon cloth substrate 12 / VC photoelectrocatalytic photoanode.
2. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, S1: bismuth hydroxide is first dispersed in ethylene glycol, and then nitric acid is added to dissolve it to obtain a mixed solution; The solvent of the ammonium molybdate solution is ethylene glycol.
3. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 2 12 / VC photoelectrocatalytic photoanode method, characterized in that, The ratio of bismuth hydroxide to ethylene glycol is 0.26 g: 10-40 mL, nitric acid is added to adjust the pH to 3-9, and then stirred until completely dissolved to obtain a mixed solution; In the ammonium molybdate solution, the ratio of ammonium molybdate to ethylene glycol is (0.196-0.588) g: (10-40) mL.
4. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, S1: adding the mixed solution and oxalic acid into the ammonium molybdate solution and stirring for 4-24 h to obtain a sol.
5. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, S2 heats the sol at 100-160 °C for 2-18 h, grinds it evenly, and finally performs heat preservation treatment at 300-800 °C.
6. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 5 12 / VC photoelectrocatalytic photoanode method, characterized in that, The heat preservation treatment described in S2 is carried out at 300-800 °C for 2-6 h, wherein the temperature is increased from room temperature to 300-800 °C at a heating rate of 5-20 °C / min.
7. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, The VC powder described in S2 is obtained by the following steps: Vanadium tetrachloride and carbon powder are uniformly mixed in a mass ratio of (0.5-3):(1-6), and then heated from room temperature to 800-1000 °C at a rate of 5-20 °C / min under the protection of an inert atmosphere, and kept at 800-1000 °C for 2-4 h. After the product is cooled, it is ground to obtain VC powder; The pickled carbon cloth described in S3 is obtained by the following steps: The carbon cloth was cut into carbon cloth blocks with a length of 20-60 mm and a width of 10-40 mm, and then the carbon cloth blocks were immersed in acetone, 3-6 mol / L HCl solution, deionized water and anhydrous ethanol in turn for ultrasonic treatment for 15-30 min to obtain the acid-washed carbon cloth.
8. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, S2 will be 0.1-0.6 g Bi2Mo3O 12 The powder is added to 30 mL-80 mL of isopropanol and dispersed evenly, and then 0.1-0.6 g of iodine is added and stirred until evenly dispersed to obtain a first precursor solution; S2: add 0.1-0.6 g VC powder to 0.005-0.05 g polyvinyl pyrrolidone and disperse evenly, then add 0.1-0.6 g iodine and stir until evenly dispersed to obtain a second precursor solution.
9. Deposition of Bi2Mo3O on a carbon cloth substrate according to claim 1 12 / VC photoelectrocatalytic photoanode method, characterized in that, S3 arranges the pickled carbon on the negative electrode of the pulse arc discharge instrument, and the positive electrode uses graphite, which is deposited at 80-150 °C. Bi2Mo3O is deposited on the carbon cloth substrate. 12 / VC photoelectrocatalytic photoanode.
10. A method of depositing Bi2Mo3O on a carbon cloth substrate according to any one of claims 1 to 9 12 Bi2Mo3O deposited on a carbon cloth substrate obtained by the VC photoelectrocatalytic photoanode method 12 / VC photoelectrocatalytic photoanode.
Citation Information
Patent Citations
Method for preparing Mo-VC nano powder coated with carbon atom layer
CN109967116A
Carbon / carbon composite material SiC / SiB6 coated Al2O3 / Glass composite anti-oxidation coating and preparation method thereof
CN116332676A
Two-dimensional transition metal compound and preparation method and application thereof based on MXene
CN116986906A
Bi2MoO6-Mo2C-C / C photoelectric catalyst as well as preparation method and application thereof
CN119144996A
Multicomponent bismuth- molybdate catalyst, preparation method thereof and method of preparing 1,3-butadiene using said catalyst
KR1020100028702A